Why attractive women want gay male friends: A previously undiscovered strategy to prevent mating deception and sexual exploitation. (1st January 2018) - Russell, Eric M.; Babcock, Meghan J.; Lewis, David M.G.; Ta, Vivian P.; Ickes, William
Abstract: Although research has begun to elucidate why women form close friendships with homosexual males, little research has investigated individual differences in women's tendency to befriend gay men. Because (1) gay men do not have the motive to mate with women or to compete with them for straight male partners and (2) attractive women are more likely to be sexually and competitively targeted by heterosexual individuals, we hypothesized that attractive women place greater value on gay's men mating advice and are more likely to befriend them. In Study 1, participants indicated their likelihood of deceiving female targets. Results revealed that more attractive targets were more likely to be both sexually deceived by straight men and competitively deceived by women. In Study 2, women created their ideal group of friends by allocating "friend dollars" to individuals of different genders and sexual orientations. More attractive women allocated more dollars to gay male friends, and this outcome was mediated by their perception that gay men would value them beyond sex and could offer them valuable mating advice. These findings suggest that befriending gay men may be an important feature of women's mating strategies, especially among attractive women who face greater mating threats from heterosexual individuals. Highlights: Attractive women may befriend gay men to mitigate heightened mating threats. Thus, we predicted that these women would value gay men's advice and friendship. Attractive women are more likely to be deceived by straight men and straight women. Attractive women place high value on gay men's nonsexual desire and mating advice. These features mediated attractive women's increased desire for gay male friends.